COMPUTATIONAL PROGRAM OF ISODOSE AND TREATMENT PLANNING SYSTEM (TPS) FOR BRACHYTHERAPY USING 125I-SEED-SOURCES - Ibon Suparman; Sunarhadijoso Soenarjo (BATAN, 2012)
ABSTRACTCOMPUTATIONAL PROGRAM OF ISODOSE AND TREATMENT PLANNING SYSTEM(TPS) FOR BRACHYTHERAPY USING 125I-SEED-SOURCES. To reach the goals of abrachytherapy treatment, a guaranteed dose rate calculation as well as a treatment planningsystem (TPS) are absolutely needed. Therefore, a local computational program for isodose andTPS calculations has been developed. The program has been performed using Microsoft VisualBasic for Windows and its supporting tools based on dosimetry calculation models developedand updated by the Association of American Physicist in Medicine. The program was startedfrom the dose rate calculation of the of 125I-seed-source assumed as a line source with 0.3 cmof active length. This program can display two dimensions-isodose contour of the single or poly-125I-seeds presented in the directions of lateral, anterior and caudal by changing the polarcoordinate system (r, θ) into a Cartesian coordinate system (x,y). The dose rate at thedistances of 1, 2, 3 and 4 cm from the center point as well as the effect of single-seed-sourcerotation can also be calculated. The entered data as well as the resulting calculation and theisodose contour presentation can be saved, quickly traced and redisplayed at any timenecessarily. It was found that this computer program is in agree with the referenced data so it ishopefully able to assist physicians in the domestic implementation of 125I seeds implants forbrachytherapy.Keywords: 125I-seed-source, brachytherapy, isodose contour, treatment planning system,computer programABSTRAKPROGRAM KOMPUTASI ISODOSIS DAN TREATMENT PLANNING SYSTEM (TPS)UNTUK BRACHITERAPI MENGGUNAKAN 125I-SEED-SOURCES Dalam aplikasi teknikbrachiterapi, perhitungan dosis dan perencanaan terapi (treatment planning system, TPS)mutlak diperlukan, oleh karena itu program komputasi lokal untuk perhitungan isodosis dan TPSperlu dikembangkan. Program komputasi isodosis dibuat menggunakan Microsoft Visual Basicfor Windows beserta perangkat pendukungnya berdasar pada model perhitungan dosimetriyang dikembangkan dan diperbarui oleh The Association of American Physicist in Medicine.Program dimulai dengan perhitungan laju dosis 125I-seed-source yang diasumsikan sebagaisumber garis sepanjang 0,3 cm. Program ini dapat menampilkan kontur isodosis dua dimensidari 125I-seed-source yang disajikan dengan arah lateral, anterior dan caudal dengan mengubahsistem koordinat polar (r, θ) menjadi sistem koordinat Cartesian (x,y). Laju dosis pada jarak 1, 2,3 dan 4 cm dari titik pusat dan efek rotasi 125I-seed-source tunggal juga dapat dihitung. Datamasukan (input) dan hasil perhitungan serta tampilan kontur isodosis dapat disimpan, ditelusuridan ditampilkan kembali secara cepat setiap saat. Hasil perhitungan isodosis dengan programkomputer ini sesuai dengan data acuan sehingga diharapkan program ini dapat membantu paradokter dalam implementasi 125I-seed-source untuk brachiterapi.Kata kunci: 125I-seed-source, brachiterapi, kontur isodosis, treatment planning system, programkomputer